FIRST REPORTED CASE OF ANTI-AMPAR ENCEPHALITIS WITH CONCURRENT MYASTHENIA GRAVIS AND THYMOMA IN VIETNAM (Vietnam Journal of Community Medicine, 2026)
Autoimmune encephalitis associated with antibodies against the alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor is a rare subtype of autoimmune encephalitis. We report the clinical presentation, laboratory findings, and treatment outcomes of the first documented Vietnamese case of anti-AMPAR autoimmune encephalitis occurring concurrently with myasthenia gravis and thymoma. The patient was a 42-year-old woman with a history of myasthenia gravis who was admitted with characteristic symptoms of limbic encephalitis, including memory impairment and confusion. Anti-AMPAR antibodies were detected in both serum and cerebrospinal fluid using indirect immunofluorescence. Chest computed tomography revealed an anterior mediastinal mass. The patient was treated with high-dose methylprednisolone and five cycles of plasma exchange. She exhibited transient improvement in consciousness and was scheduled for surgical resection and histopathological evaluation of the mediastinal mass; however, due to the high surgical risk, the procedure was not performed.
Keywords: autoimmune encephalitis, AMPA receptor, thymoma, myasthenia gravis